Takāmul al-ʿAqīdah wa-al-Akhlāq li-al-Wiqāyah min al-ʿUnf: "al-Nār ʿalā Adnā al-Ẓulm" fī al-ʿAṣr al-Raqmī - Habibi Hamzah; M Kholid Muslih; Jarman Arroisi (Al-Zahra : Journal for Islamic and Arabic Studies, 2026)
This study is motivated by the increasing phenomenon of moral decline and violence in both social and digital spaces, amid the limitations of aqidah and akhlaq education that remains general in responding to subtle forms of deviant behavior. The study aims to offer an integrative concept between aqidah and akhlaq through a partial approach based on the concept of “Hell for the slightest injustice” as a foundation for preventive anti-violence education. This study employed a qualitative method using library research, complemented by a philosophical approach to examine the ontological, epistemological, and axiological foundations of the relationship between aqidah and akhlaq. Data were collected from the Qur’an, Prophetic traditions, classical Islamic texts, and relevant contemporary academic literature. The data were analyzed through a conceptual approach and content analysis using descriptive-analytical methods to examine the relationship between aqidah, akhlaq, and violence prevention. The findings indicate that this concept has a strong normative basis in Islamic teachings and emphasizes that every form of injustice, no matter how small, carries moral and eschatological consequences. In addition, belief in the Day of Judgment functions as a mechanism of self-control in preventing deviant behavior. The study also proposes the concept of “micro-injustice” as a development of Islamic ethical studies in addressing contemporary issues such as cyberbullying. It concludes that the integration of aqidah and akhlaq based on awareness of God's supervision and fear of Him represents a promising model for moral education in the digital era.